2021
DOI: 10.1177/15280837211010666
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation properties and thermogravimetric analysis of 3D braided flax PLA textile composites

Abstract: Recent advances in the development and application of bio-based (natural fiber and biopolymer) composites are gaining broad attention because the resulting polymer completely degrades and does not release harmful substances. In this study, natural fiber 3 D braided yarn textile PLA (Polylactic acid) bio-composites are developed by film sequencing followed by hot-press compression molding. Bio-deterioration and thermal stability of the composites are analysed for storage, machining, transportation, and in-servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…The purpose of these modi cations is to improve the overall performance and properties of the composite by building a stronger and more effective bonding between the reinforcing bers and the matrix [16][17][18]. Helicteres isora and PLA composites were fabricated using a combination of solution casting and compression moulding techniques [19]. Density, void content, water absorption behavior, Tensile and exural properties, along with failure surface morphology using Scanning Electron Microscopy (SEM) images, and thermal properties of the composites were studied.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of these modi cations is to improve the overall performance and properties of the composite by building a stronger and more effective bonding between the reinforcing bers and the matrix [16][17][18]. Helicteres isora and PLA composites were fabricated using a combination of solution casting and compression moulding techniques [19]. Density, void content, water absorption behavior, Tensile and exural properties, along with failure surface morphology using Scanning Electron Microscopy (SEM) images, and thermal properties of the composites were studied.…”
Section: Introductionmentioning
confidence: 99%
“…The literature reveals varying results in terms of biodegradability. Some studies [18][19][20][21][22][23] suggest that PLA biodegrades slowly, but the process accelerates with the addition of natural fibres. In contrast, a study by Mathew et al [24] revealed that the addition of microcrystalline cellulose (MCC) decreased the biodegradation rate.…”
Section: Introductionmentioning
confidence: 99%
“…24 Epoxy/30 wt% Pineapple leaf/10 wt% Pineapple leaf particulates 0.88 Saha et al 25 Vinyl ester/15 wt% Coir fiber/10 wt% Aramid fiber/5 wt% coconut shell powder 1.15 Udaya Kumar et al 26 Epoxy/50 wt% palm tree leaf stalk 1.61 Alshammari et al 27 Polyester/2 wt%Aegle Marmelos/9 wt% Terminalia chebula/6 wt% Soap nuts 0.89 Prasad et al 28…”
mentioning
confidence: 99%